2021
DOI: 10.3389/fneur.2021.648548
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Multi-Modal MRI for Differentiating of Parkinson's Disease and Progressive Supranuclear Palsy Using Machine Learning

Abstract: Background: Patients with Parkinson's disease (PD) and progressive supranuclear palsy Richardson's syndrome (PSP-RS) often show overlapping clinical features, leading to misdiagnoses. The objective of this study was to investigate the feasibility and utility of using multi-modal MRI datasets for an automatic differentiation of PD patients, PSP-RS patients, and healthy control (HC) subjects.Material and Methods: T1-weighted, T2-weighted, and diffusion-tensor (DTI) MRI datasets from 45 PD patients, 20 PSP-RS pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…Both the two datasets had good classification performance, which further indicated the good classification performance and generalization of our model. Third, it has been reported that combining multimodal data and clinical data can improve the performance of the machine learning model (Shi et al, 2021a;Talai et al, 2021), but the primary set in this study only contained ALFF data. A subsequent study should incorporate other modal MRI data, metrics, and clinical data to construct and evaluate the model.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Both the two datasets had good classification performance, which further indicated the good classification performance and generalization of our model. Third, it has been reported that combining multimodal data and clinical data can improve the performance of the machine learning model (Shi et al, 2021a;Talai et al, 2021), but the primary set in this study only contained ALFF data. A subsequent study should incorporate other modal MRI data, metrics, and clinical data to construct and evaluate the model.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have confirmed the value of rs-fMRI in neuropsychiatric diseases ( Szewczyk-Krolikowski et al, 2014 ; Hu et al, 2015 ; O’Callaghan et al, 2016 ). Recently, with the development of machine learning technologies, more and more studies have used machine learning methods to explore the classification, prognosis prediction, and physiological mechanism of neuropsychiatric diseases, including PD ( Cao et al, 2020 ; Lin et al, 2020 ; Pang et al, 2021 ; Shu et al, 2021 ; Talai et al, 2021 ; Zhang et al, 2021 ). The ROI-based feature extraction is the most commonly used feature extraction method ( Wang L. et al, 2020 ; Zhao et al, 2020 ; Shi et al, 2021b ; Talai et al, 2021 ), and it is a useful method to reduce the data dimensionality ( Wang L. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, we assessed only NM-MRI in the present study since we focused on dopaminergic neurons to assess their functional recovery. However, recent studies reported that multimodal MRI assessments including not only NM-MRI, but also structural imaging, nigrosome imaging, iron-sensitive imaging, diffusion tensor imaging (DTI), arterial spin labeling (ASL), and resting-state fMRI to assess functional connectivity would be effective to diagnose PD and understand pathophysiological mechanisms of PD symptoms (Bae et al, 2021;Heim et al, 2017;Talai et al, 2021). Although the present study does not provide information on full pathophysiological changes in the patient, the results suggest that NM-MRI may be useful to assess responses of dopaminergic neurons to treatments.…”
Section: Discussionmentioning
confidence: 99%